Serum Concentration of Zinc in Healthy Pregnant Women Versus Pre-Eclamptic Pregnant Women: A case Control Study in Lahore, Pakistan (Medical Forum Monthly, 2024)
Objective: To find out serum zinc level in healthy pregnant women and pre-eclemptic pregnant women.Study Design: Ramdomized controlled trial studyPlace and Duration of Study: This study was conducted at Department of Pathology, Lady Willingdon Hospital, Lahore and at Lahore College for Women University, Lahore from March 2015 to September 2015.Materials and Methods: Size of sample was determined statistically by using table and119 (102 experimental group(51 pre-eclamptic pregnant women and 51 normal pregnant women) and 17 control group) blood samples were collected randomly. Results: The average zinc concentration in healthy pregnant group was found 1.44 ± 0.14 mg/l as compared to pre-eclamptic pregnant group 0.25 ± 0.02 mg/l. In pregnant women average zinc concentration was found to be decreasing with trimester. The average systolic blood pressure in healthy pregnant women was 113.83±1.74 mm/Hg as compared to the pre-eclamptic pregnant women was 145.34±1.68 mm/Hg. Average diastolic blood pressure in healthy pregnant women, was found 75.23±1.46 mm/Hg as compared to pre-eclamptic pregnant women, which was 92.76±1.80 mm/Hg.Conclusion: Zinc level in the blood serum of pre-eclamptic pregnant women was found lower as compared to healthy pregnant women. Low blood serum zinc level is associated with the elevated systolic and diastolic blood pressure also.